2021
DOI: 10.1097/ta.0000000000003494
|View full text |Cite
|
Sign up to set email alerts
|

The use of predefined scales and scores with eye-tracking devices for symptom identification in critically ill nonverbal patients

Abstract: BACKGROUND:Eye tracking (ET) may be a novel tool to enable nonverbal communication. We hypothesized that ET could be used successfully by intensive care unit (ICU) patients with artificial airways to express their levels of pain and mood, quality of life, and self-esteem with predefined scales and scores. METHODS:Prospective, monocentric, observational study, including patients with an endotracheal tube or tracheostomy tube and a history of mechanical ventilation for more than 48 hours without delirium, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The prototype of symptom assessment in patients able to self-report is pain assessment, and the most basic form of general symptom assessment in patients with communication difficulties is asking yes/no questions (Chanques et al, 2015). Existing assessment tools have limited usability for patients with communication impairments (Ull et al, 2022), but Choi et al (2017) offer a description of how to facilitate symptom assessment in non-vocal ICU patients, emphasizing the need to adapt the assessment to the communication abilities of the patient, and minimizing the burden of the assessment for the patient. When patients are unable to self-report, symptoms are assessed by observing behaviour, observations by proxies, or by assuming the presence of symptoms under certain circumstances (Choi et al, 2017;Devlin et al, 2018;Puntillo et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The prototype of symptom assessment in patients able to self-report is pain assessment, and the most basic form of general symptom assessment in patients with communication difficulties is asking yes/no questions (Chanques et al, 2015). Existing assessment tools have limited usability for patients with communication impairments (Ull et al, 2022), but Choi et al (2017) offer a description of how to facilitate symptom assessment in non-vocal ICU patients, emphasizing the need to adapt the assessment to the communication abilities of the patient, and minimizing the burden of the assessment for the patient. When patients are unable to self-report, symptoms are assessed by observing behaviour, observations by proxies, or by assuming the presence of symptoms under certain circumstances (Choi et al, 2017;Devlin et al, 2018;Puntillo et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…This is one reason: We believe that the results from Bodet-Contentin substantially underestimate the ability of their patients to thoughtfully communicate by using the eye-tracking technology. Another reason lies in the observation that intubated critically ill patients can consistently report on their appraisals of their situation via eye fixations on response panels [ 6 ]. For instance, 90% indicate to feel trapped (while other items show lower approval rates).…”
mentioning
confidence: 99%
“…Accounting for the high level of concentration required by the patients their motivation to give answers might be reduced. Beyond the example just mentioned, in several studies it has been shown that critically ill patients are quite able to give differentiated answers questions concerning their actual situation, requirements, and projections on their future [ 3 – 6 ]. Thirdly, although automation of tasks will allow the medical personal on an ICU to focus on other duties, in this particular setting, we feel that a personal interaction with a human being would be preferable.…”
mentioning
confidence: 99%
See 2 more Smart Citations